Frightening or Foolish? Gendered Perceptions of Public Intoxication Among Youths and Adults in Norway and Finland. (1st January 2020) - Scheffels, Janne; Moan, Inger Synnøve; Simonen, Jenni; Tigerstedt, Christoffer
Abstract: Background : What people define as acceptable alcohol use may differ between social situations and depend upon on who is drinking as well as who is evaluating the situation. Objective : The aim of the study was to explore how Norwegian and Finnish youth and adults perceived the acceptability of situations involving public intoxication and how gender and alcohol's harm to others were made relevant in their reflections. Methods : We conducted eight focus groups among adolescents ( N = 44) and eight among adults ( N = 38), using photos and stories of drinking situations as stimuli for the discussions. Results : Youths' and adults' perceptions of public intoxication were characterized by ambivalence: negative evaluations were often nuanced and negotiated while positive evaluations typically were followed up with reservations. To some extent, their evaluations depended upon the gender and age of the drinker. Although a norm of gender equality was emphasized, women were typically criticized for their looks and for foolish behavior when drunk, while drunk men were often perceived as frightening. Age was a prominent dimension in evaluations of the acceptability of women's alcohol use, while it was seldom mentioned when discussing intoxicated men. Youths seemed to have somewhat more restrictive attitudes towards public intoxication than adults, reflecting perhaps how they related to the situations with more general conceptions of drinking and harms from drinking, picked up from public debate or from school. Conclusion : Perceptions of alcohol's harm to others were clearly gendered, in that intoxicated men were seen as frightening while women were seen as foolish.